A simple iterative method for the analysis of plane trusses. (June 2020) - Mojtaba Hozhabrossadati, Seyed; Aftabi Sani, Ahmad
Abstract: In this article, a simple iterative method is proposed for the analysis of plane trusses. The main idea of the approach is taken from Kani's method. Unlike most schemes, the present method does not need to solve systems of equations to obtain problem solution. Therefore, the computational costs dramatically decrease. On solving the problem, the internal forces of the truss are found. To verify the proposed solution, the proposed outcomes are compared with those of matrix analysis.